Lightning activities in Venezuela using the Lightning Imaging Sensor of TRMM NASA project - Martínez, M.; Ramírez, J.; Montaño, R. (Rev. Téc. Fac. Ing. Univ. Zulia)
<!–[if gte mso 9]> Normal 0 21 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> In this work, handlings of the NASA LIS data were presented, to establish the lightning activities in Venezuela, between years 1998 and 2002.The main objective is to obtain the most relevant data, discerning by geopolitical State and month along the year. With this processing, is possible to show the geographical areas with the highest lightning activity and the variation of this characteristic with the months along the years considered. This information is very important to engineers and Scientifics to know the most recent data of the lightning by Venezuelan Regions and specifically for high risk zones, like that involved in oil exploration and production facilities. Finally, an iso-keraunic map, was obtained.